Development of Spinal Circuits for Swimming in Zebrafish (DANIO RERIO) LARVAE. Emphasizing on the Rhythm Generation Mechanism - Roussel, Yann (Université d'Ottawa / University of Ottawa, 2018)
It has long been established that the spinal cord is able to produce locomotor activity on its own. Despite extensive research identifying and describing the involvement of multiple spinal neuron populations that are part of the spinal locomotor circuit, the manner in which these different components act together to precisely control the rhythm and the pattern of activation of muscles during locomotion remains largely undetermined. We sought to shed light on how the components of spinal locomotor circuits interact to produce robust locomotion using a developmental approach in zebrafish larvae. We used electrophysiological techniques to observe how the rhythm generation mechanism developed while the fish was transitioning from an early form of swimming to a more mature swimming behaviour. In the process we were able to highlight fundamental changes in the organization of spinal locomotor circuits as its operation moves from a pacemaker-based architecture relying on intrinsic properties of neurons to a network oscillator-based architecture relying on synaptic connectivity to generate proper rhythm driving the fish tail beats. Additionally, we revealed that this transition occurred at different times along the spinal cord progressing in a caudorostral direction. By combining these experimental observations with already published insights we were able to propose models of spinal locomotor circuits reproducing the successive locomotor behaviours encountered through development. By incrementing supplementing the circuit model in a manner that reflected biological processes by which the nervous system maturates (neurogenesis, synaptic connectivity refinement and maturation of intrinsic properties) we mirrored the natural development of the spinal locomotor circuit. This series of successively constructed models permitted us to pinpoint possible roles of specific neural populations for swimming behaviour as well as eventual targets and mechanism of actions of neuromodulators (serotonin and dopamine). In the process, I further provided testable hypotheses for future inquiries. Overall, the experimental findings in combination with the modeling work are an important step forward in fully understanding how the spinal cord generates swimming movements in zebrafish.
Keywords: Locomotion; CPG; Spinal cord; Zebrafish; Devlopment; Modeling; Pacemaker; Half-centre oscillators; Rhythm generation